Factors influencing fidelity to guideline implementation strategies for improving pain care at cancer centres: a qualitative sub-study of the Stop Cancer PAIN Trial - Tim Luckett; Jane Phillips; Meera Agar; Linda Richards; Najwa Reynolds; Maja Garcia; Patricia Davidson; Tim Shaw; David Currow; Frances Boyle; Lawrence Lam; Nikki McCaffrey; et al. (BMC, 2024)
Abstract Background The Stop Cancer PAIN Trial was a phase III pragmatic stepped wedge cluster randomised controlled trial which compared effectiveness of screening and guidelines with or without implementation strategies for improving pain in adults with cancer attending six Australian outpatient comprehensive cancer centres (n = 688). A system for pain screening was introduced before observation of a 'control' phase. Implementation strategies introduced in the 'intervention' phase included: (1) audit of adherence to guideline recommendations, with feedback to clinical teams; (2) health professional education via an email-administered 'spaced education' module; and (3) a patient education booklet and self-management resource. Selection of strategies was informed by the Capability, Opportunity and Motivation Behaviour (COM-B) Model (Michie et al., 2011) and evidence for each strategy's stand-alone effectiveness. A consultant physician at each centre supported the intervention as a 'clinical champion'. However, fidelity to the intervention was limited, and the Trial did not demonstrate effectiveness. This paper reports a sub-study of the Trial which aimed to identify factors inhibiting or enabling fidelity to inform future guideline implementation initiatives. Methods The qualitative sub-study enabled in-depth exploration of factors from the perspectives of personnel at each centre. Clinical champions, clinicians and clinic receptionists were invited to participate in semi-structured interviews. Analysis used a framework method and a largely deductive approach based on the COM-B Model. Results Twenty-four people participated, including 15 physicians, 8 nurses and 1 clinic receptionist. Coding against the COM-B Model identified 'capability' to be the most influential component, with 'opportunity' and 'motivation' playing largely subsidiary roles. Findings suggest that fidelity could have been improved by: considering the readiness for change of each clinical setting; better articulating the intervention's value proposition; defining clinician roles and responsibilities, addressing perceptions that pain care falls beyond oncology clinicians' scopes of practice; integrating the intervention within existing systems and processes; promoting patient-clinician partnerships; investing in clinical champions among senior nursing and junior medical personnel, supported by medical leaders; and planning for slow incremental change rather than rapid uptake. Conclusions Future guideline implementation interventions may require a 'meta-implementation' approach based on complex systems theory to successfully integrate multiple strategies. Trial registration Registry: Australian New Zealand Clinical Trials Registry; number: ACTRN 12615000064505; data: https://www.anzctr.org.au/Trial/Registration/TrialReview.aspxid=367236&isReview=true .